Proprioception influence in the balance of gymnastics rhythmic postural athletes. - Semeão, Florisvaldo Aparecido; Hirata, Ana Claudia de Souza; Bertin, Larissa Dragonetti; Oliveira, Rodrigo Franco de (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Rhythmic gymnastics (RG) is a sport that combines art biomechanical gestures of high complexity, which requires a high level of development of physical qualities such as agility, flexibility, strength, impulsion and dexterity. In this modality studies show that injuries are attributed more articulate knees, ankles, and in some cases ends wrist sprains being the most frequently recorded in athletes in competition level. Therefore, proprioception and muscle control play a fundamental role in dynamic joint stability, since after orthopedic injuries sensorimotor some characteristics are altered and should be focused on rehabilitation programs to get a better return so the activities prior to the injury. Objective: The objective of this project is to evaluate the effect of proprioceptive training on postural balance of athletes in rhythmic gymnastics - RG, from the use of a force platform BIOMEC400 (EMG System do Brazil, Ltda SP). Method: We performed a proprioceptive training in thirty days, in two stages, moving the complexity of the exercises each phase proprioceptive training. Results: We observed that there was a significant improvement in results of training, when it was used more complex exercises and agility exercises before. Conclusion: Because it is athletes RG high performance and present a predominance of activities in one foot, protocols proprioception should be more intensively, generating a higher level of disturbance and postural imbalances.